Bearing characteristics and continuous–discontinuous numerical analysis of a pressure grouting pile in a calcareous sand foundation - Qifen Cheng; Jianlin Li; Jie Liu; Shifu Qin; Tongqiang Xiong; Ge Zhang (Scientific Reports)
Abstract The complex mechanical characteristics of calcareous sand complicate comprehensive analysis of the bearing characteristics of pressure grouting piles. The bearing mechanism of pressure grouting piles is unclear. Field tests of the bearing characteristics of pressure grouting piles in calcareous sand foundations were carried out. On the basis of the field test data, the coupled finite difference method (FDM) and discrete element method (DEM) were applied to explore the settlement characteristics. The force transfer laws in calcareous sand foundations are analyzed using complex network theory. The results show that the ultimate bearing capacity of pressure grouting piles increases significantly with increasing pile diameter. An increase in the pile‒soil interface friction coefficient can increase the pile side friction resistance, which can then increase the ultimate bearing capacity of the pile foundation. The friction coefficient of calcareous sand foundations can also increase the ultimate bearing capacity of pile foundations. However, the settlement of the pile foundation also increases. The axial force of the grouting pile gradually increases as the burial depth increases. When the pile bottom is reached, the axial force of the pile body clearly increases. This study presents an effective tool for the comprehensive analysis of the bearing characteristics of pressure grouting in calcareous sand foundations.